Present and potential distribution of the cacti Ferocactus histrix, Mammillaria bombycina and M. perezdelarosae in the state of Aguascalientes, Mexico - Meza Rangel, Ernestina; Tafoya, Felipe; Lindig Cisneros, Roberto; Sigala Rodríguez, José Jesús; Pérez Molphe-Balch, Eugenio (Instituto de Ecología, A.C., 2014)
The Cactaceae is a representative group of the national flora of Mexico that faces conservation problems due to overexploitation and illegal trade at the national and state levels. In this paper the present distribution of three cactus species protected by Federal Law (Ferocactus histrix, Mammillaria bombycina and M. perezdelarosae) occurring in the state of Aguascalientes is updated and their potential distribution estimated using ecological niche modeling techniques. Most populations of F. histrix were found in the western half of the state of Aguascalientes at elevations between 1750 and 2473 m, in canyons of difficult access or low hills. The populations of M. bombycina were located in southwestern Aguascalientes at elevations between 1847 and 2417 m, in canyon walls and in horizontal terrain close to the cliffs. Finally, populations of M. perezdelarosae were located in the southwestern and central regions of the state on exposed bedrock at elevations between 2024 and 2417 m. This study contributes to our knowledge of the distribution and the populations of all three species, which may be used for future reintroduction and conservation efforts of these species in the state of Aguascalientes.